Intellectual properties of the Federal Network of Professional, Scientific and Technological Education - Prado, Junior Leal do; Fernandez-Crehuet, Jose Maria; Oliveira Júnior, Antonio Martins de (Education Policy Analysis Archives, 2017)
The Federal Network of Professional, Scientific and Technological Education (FNPSTE), established by Law nº 11,892/2008, presents an innovative institutional model in terms of the political-pedagogical proposal, and it is expected that its institutions comply with the Technological Innovation Law by creating the Technological Innovation Centers (TICs). Among the responsibilities of TICs, the protection of intellectual properties generated in the institutions is highlighted. In this article, we present a study of the databases of the National Institute of Industrial Property and the Ministry of Agriculture, Livestock and Supply to evaluate the protection of intellectual properties claims by the TICs of the institutions of FNPSTE in the period from 2009 to 2015, in addition to highlighting the impact of education policies on the expansion of the FNPSTE. Although implementation of TICs is not consolidated in all institutions of FNPSTE, it is noted through the results that in recent years the implementation of TICs has presented a significant and relevant growth of intellectual properties. The institutions of Northeast, South and Southeast regions of Brazil have a greater number of intellectual properties when compared to Midwest and North regions, pointing out the need for greater investments in public policies in order to promote applied research and, consequently, technological innovation.